The equalization scheme of the residual voluntary health insurance in Slovenia - Zgrablić, Boris (Ars mathematica contemporanea, 2015)
Residual voluntary health insurance in Slovenia covers the difference between the (recognised) value of the health service and the part of this value that is payed by the compulsory health insurance. From the inception of compulsory health insurance in 1992, residual voluntary health insurance has open enrolment. From 2006 community rating applied, as well as an equalization scheme with which the differences in health services expenses, arising from the different structures of the insurees of the single insurance undertakings regarding age and gender, shall be equalized. The equalization scheme of the residual voluntary health insurance in Slovenia is presented, along with a detailed explanation of the formulae required for the computation.
Keywords: claims equalization; dopolnilno prostovoljno zdravstveno zavarovanje; equalization scheme; izravnalna shema; izravnava tveganj; izravnava zahtev; residual voluntary health insurance; risk equalization